Youth Leisure Issues - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 1991)
Leisure is very important area of life for youth. During leisure time young people can fully express their "I", satisfy their tastes and inclinations. In addition, leisure includes the least formalized activities, so here young people feel most free and independent. On the other hand, leisure form are highly dependent on the conditions. These should be such that young people choosing freely could express themselves, but would not become the subjects of deviant behaviour. The article, based on a quantitative survey, analyses the nature of youth leisure, its trends, and barriers in its organization. It also examines the connections of youth leisure with their parents’ social situation, young people’s sex, age, type of school attended. Another very important aspect of the study was the deviant behaviour of the youth, bad habits. A direct link was discovered between this aspect and improper way of spending leisure time. It is also predicted that increasing domination of commercial relationships in culture, sports and entertainment, can greatly exacerbate the problem of youth leisure activities and may lead to many negative long-term consequences.